Short, medium and long-term performance of Initial Public Offerings in South Africa: JSE Alt-X versus JSE Main Board: the post-JSE Alt-X evidence (2004-2007) - Manikai, Bothwell (My University, 2011)
This study has been prompted by the recent introduction of the JSE Alternative Exchange in South Africa, an alternative listing platform for smaller companies compared to the more established JSE Main Board Exchange. This new era has led to information asymmetry among current and prospective investors regarding the risk-return profile of the companies listed on the relatively new JSE Alternative Exchange and how this profile relates to the profile of firms listed on the long established JSE Main Board Exchange. In an attempt to fill the above information gap, this study sheds light on the short, medium and long-term performances of initial public offerings of companies listed on the JSE Alternative Exchange vis-a-vis that of JSE Main Board Exchange. This information is relevant for investment and financing decision making, principally for investors, venture capitalists and entrepreneurs. The findings of this research appear to be contrary to expectations and to corporate finance theory. The results indicate that on average, initial public offerings by larger JSE Main Board companies outperform the smaller JSE Alternative Exchange companies on a nominal and risk-adjusted bases in the short-medium and long-term. It must be noted however that the differences in performance are not statistically significant. On the other hand, in line with documented evidence in the literature, it was found that the risk of returns on the smaller capitalisation JSE Alternative Exchange companies was indeed higher than that of the JSE Main Board companies. A similarity identified between the average performances of the two listing platforms is that, the returns for companies decreased overtime between the short and long-term. This may be partly due to the impact of the 2007 economic recession.
Keywords: Johannesburg Stock Exchange; JSE Alternative Exchange; JSE Main Board Exchange; Venture capital; Small business